2021
DOI: 10.14202/ijoh.2021.232-236
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of extended-spectrum β-lactamase-producing Escherichia coli in companion dogs in animal clinics, Surabaya, Indonesia

Abstract: Background and Aim: The practice of keeping animals as pets is becoming increasingly common. The upsurge of extended-spectrum β-lactamase (ESBL)-producing organisms of animal origin is a health threat globally. This study aimed to identify the presence of extended-spectrum β-lactamase-producing Escherichia coli in companion dogs in animal clinics in Surabaya, Indonesia. Materials and Methods: A total of 85 rectal swab samples were collected from companion dogs at five animal clinics in different regions of Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Due to its easy application, time-and cost-effectiveness, the VITEK ® 2 system is being increasingly used in everyday practice [50]. This system efficiently identifies Staphylococci species, MRS, and other bacterial species [33,[51][52][53]. In our study, the Kappa analysis showed almost perfect agreement between the VITEK ® 2 system and molecular methods for overall identification.…”
Section: Discussionsupporting
confidence: 53%
“…Due to its easy application, time-and cost-effectiveness, the VITEK ® 2 system is being increasingly used in everyday practice [50]. This system efficiently identifies Staphylococci species, MRS, and other bacterial species [33,[51][52][53]. In our study, the Kappa analysis showed almost perfect agreement between the VITEK ® 2 system and molecular methods for overall identification.…”
Section: Discussionsupporting
confidence: 53%
“…Biochemical substrates utility profile-based VITEK ® 2 Compact automation was used in this study. It is a reliable method and has been used in several previous veterinary studies [32][33][34]. However, Crawford-Miksza et al [35] reported the misidentification of the variant biotype of E. coli O157:H7 as Escherichia fergusonii.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study conducted by Lukman et al [31], ESBL-producing E. coli was present in broiler feces in Bogor, Indonesia, which was related to the findings in this study. The results of this study are in accordance with several studies in Indonesia which reported that the ESBL-producing E. coli were identified from feces of broilers in Bogor reached 25% [32]; cloacal swabs of broilers from wet markets in Surabaya [23]; cloacal swab of layers in Blitar reached 7.03% [28]; swab cages and wastewater around broiler farm in Pasuruan 9.14% [33]; samples of chicken meat sold at Purwokerto's market reached 7.14% [34]; from environmental samples of dairy farms in Yogyakarta, Probolinggo, and East Java [35][36][37]; and from companion dogs in Surabaya reached 9.41% [38]. These findings were also similar to those reported by Lemlem et al [24], who detected blaCTX-M and blaTEM from broilers in Malaysia.…”
Section: Sample Code Esbl Gene Blatem Blactx-m Blashvmentioning
confidence: 99%
“…Gundran et al [39] also reported the detection of blaCTX-M and blaTEM in broilers from the Philippines. Numerous studies have reported that the same isolates have multiple beta-lactamase genes [38,39]. Recently, blaCTX-M was identified as the leading ESBL gene in the world [24,39].…”
Section: Sample Code Esbl Gene Blatem Blactx-m Blashvmentioning
confidence: 99%